Nilotinib and imatinib: potential candidates for treatment of dementia and Parkinson’s disease through national health insurance data - Song, Jihun; Park, Sun Jae; Kim, Yu-Jin; Park, Sang Min (Frontiers in Neurology, 2025)
BackgroundReal-world evidence on the potential of tyrosine kinase inhibitors (TKIs) for dementia and Parkinson’s Disease (PD) is crucial. This observational study aimed to evaluate TKIs, particularly nilotinib and imatinib, as potential therapeutic agents for these conditions.MethodsIn this retrospective cohort study, 5,579 cancer patients who were prescribed TKIs (users; ≥ 40 years) within 5 years were used, while propensity score-matched patients without any record of TKIs (never users) served as the reference. An association of TKIs with dementia and PD was assessed by the Fine-Gray Model with adjusted-competitive hazard ratios (aCHRs) and 95% confidence intervals (CIs): [aCHRs (95% CIs; p-value)].ResultsThe risk of dementia decreased when all types of TKIs [0.65 (0.48–0.88; <0.01)], imatinib [0.66 (0.48–0.89; <0.01)], and nilotinib [0.46 (0.23–0.93; <0.05)] was used in cancer patients. Additionally, the reduced risk of PD was identified in users of all [0.56 (0.33–0.97; <0.05)] and imatinib [0.55 (0.32–0.96; <0.05)]. When the risk was evaluated according to the number of times for total usage, the aCHRs for PD in the low, middle, and high-frequency groups were 0.46 (0.20–1.02), 0.78 (0.40–1.54), and 0.40 (0.15–1.05), respectively. The risk of dementia was 0.68 (0.46–0.99), 0.57 (0.36–0.90), and 0.71 (0.44–1.17) in order of frequency (from low to high).ConclusionAs an observational study indicated a decreased risk of dementia and PD with long-term TKI use, imatinib and nilotinib may serve as potential therapeutic agents for these conditions, with more evidence from rigorous clinical trials to validate.